New traces of regulation of information platforms and a platform-based economy for the new public good - Dunayev, Ihor; Kovalenko, Mykola (Pressing Problems of Public Administration, 2022)
The paper offers the authors’ vision of a new problem for Ukraine, but not new for the Western and Eastern world – how to regulate some rising information platforms and the platform-based economy. The purpose of this article is to critically analyze the current global practice of public regulation of information platforms and, based on this, to determine new trajectories of their regulation for the greater public good and renewal of public administration.The step-by-step logic of the presentation of further material in the article is as follows: 1) critical generalization of the essential effects of information platforms for the economy and public administration; 2) modern transformations in the essence of the platform economy; 3) an overview of the essence of the existing state regulation of platforms, which departs from the regulation of purely competition, and is more aimed at the regulation of socio-economic development, 4) clarify the state and supranational regulatory approaches to platforms and the directions of their changes now in the Western world.In general, the paper is a continuation of the ongoing broad expert and political debates about what, how and who to regulate in the new platform environment, the participants of which are or soon will be almost all people. The authors pay considerable attention to the overview of regulatory issues, practices and approaches, and in particular to the latest European laws on digital markets and digital services. Together, these two laws establish a new trend to regulate not only competition, but also very broad socio-economic processes in countries that have already encountered practical difficulties in social transformations and conflicts, and this process will definitely not be quick.